Pengaruh Model Discovery Learning Terhadap Kemampuan Matematika Permulaan Anak Kelompok B Di RA Adabiyah Lais Kabupaten Musi Banyuasin - Sabriena Aisyah Putri; Lidia Oktamarina; Mardiah Astuti (JEMS: Jurnal Edukasi Matematika dan Sains, 2023)
The problem in this study is the low ability of children in beginning mathematics and to find out whether the discovery learning model has an effect on the initial math skills of group B children in RA Adabiyah Lais, Musi Banyuasin district. This type of research is Pre-Experimental with One Group Pretest-Posttest design (one group of subjects). The number of samples of children is 15 children. Data collection techniques in research using pretest and posttest. The data analysis technique used in this study uses the normality test, homogeneity test and hypothesis testing. The results of the study can be concluded that there is a significant influence between the discovery learning model and beginner mathematics. obtained tcount = 6.363 while ttable = 1.76131 because tcount = 3.363 > ttable = 1.76131. So it can be concluded that Ho is rejected, then Ha is accepted, meaning that there is a statistically significant difference in the initial mathematical ability of the children in group B RA Adabiyah Lais before and after being treated using the discovery learning model.